PARENTS-CHILD INTERPERSONAL COMMUNICATION PATTERNS IN SELF-REGULATED LEARNING (INDEPENDENT LEARNING) OF EAST KALIMANTAN STATE MADRASAH ALIYAH STUDENTS - Wijaya, Ida Suryani; Armella, Rega (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This research investigates parent-child interpersonal communication patterns in self-regulated learning (independent learning) of east Kalimantan state madrasah aliyah students. Learning independence is an essential skill in education that allows students to manage, organize, and supervise their learning process. This research uses a qualitative approach with interview and observation methods as data collection tools. Participants in this research were Madrasah Aliyah students in East Kalimantan and the students' parents. The collected data is then analyzed by paying attention to interpersonal communication patterns between parents and children during the learning process. The research results show that communication between children and parents plays a significant role in forming students' character and independent learning abilities. Open and honest communication influences children's confidence in their talents and interests. This also positively impacts students' active learning, discipline, and responsible attitude toward learning tasks and obligations. The role of parents in children's independent learning is evident in various aspects. The implication of this research is to provide recommendations for MAN East Kalimantan and related parties to increase the role of parents in supporting students' independent learning. It is hoped that the results of this research will provide an essential contribution to further understanding the relationship between parent-child interpersonal communication and students' independent learning abilities, which in turn can improve the quality of education at MAN East Kalimantan and similar educational institutions.